Attachment styles, parenting styles and theory of mind: an exploration of their relationships with social deficits in Autism Spectrum Disorder - Bailey, Nakeeta Catherine (Department of Psychology, 2017)
Autism Spectrum Disorder (ASD) is fundamentally characterised by social deficits. It is thus important to understand social functioning and what contributes to social development in children on the spectrum. It is widely accepted that ASD has a neurobiological basis, however research on understanding the lack of social skills found in ASD individuals remains indefinite and controversial. In this thesis we explored attachment styles, parenting styles and ToM to discern how they relate to social deficits in ASD. The literature for typically developing children has illustrated important relationships however there is a lack of exploration in the ASD populace. This protocol was divided into two studies. Study 1 assessed social deficits, attachment and parenting styles in 46 children with ASD aged 4 – 14 years and included both verbal (n = 19) and non-verbal (n = 27) children. The ADOS-2, Attachment Style Classification Questionnaire, and Parenting Style Dimension Questionnaire were used to measure these variables. Study 2 assessed ToM capacity and its relationship with parenting styles and social deficits in verbal children with ASD. In Study 1 we found verbal and non-verbal subgroups differed on social deficits. The aims for exploring attachment and parenting styles were to discern 1) what style dominates; 2) whether attachment and parenting styles differ between verbal and non-verbal children and 3) whether these variables relate to social deficits. We found odd patterns of attachment with no clear dominant style in our full sample. Only the non-verbal subgroup showed a relationship between secure attachment and reduced social deficits. In terms of parenting, the authoritative style was reported to be mostly employed by our parents and it related to reduced social deficits in both the full sample and the verbal subgroup. In Study 2 we explored 1) the extent of ToM deficits in ASD; 2) how parenting styles relate to ToM and 3) whether better ToM and parenting in combination related to reduced social deficits. We found severe ToM deficits in our sample which suggests delayed development. Authoritative parenting was significantly related to better ToM capacities. Furthermore, a regression of positive parenting and ToM abilities in combination with social deficits indicated that only ToM and age predicted less social deficits. This current study suggests that specifically authoritative parenting and ToM skills may be important underlying mechanisms for better social abilities in ASD. Most notably, it stresses that ASD cannot be regarded as a homogenous population as a clear distinction between the verbal and non-verbal subgroups is reported herein; a currently underestimated notion. Although still in its preliminary stages, the work reported in this thesis opens up a new line of thinking that could, in principle prove to be beneficial to research in the area of ASD.